INOVASI MAL PELAYANAN PUBLIK DI KOTA TANGERANG SELATAN - Ratih Dwi Lestari; Riska Sarofah; Fitri Susiswani Isbandi; Slamet Setiawan; Yusuf Fadli (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purpose of this study is to discuss the innovation of the Public Service Mall in South Tangerang City as a forum for Regional Apparatus Organizations in improving the quality of public services in South Tangerang City. This research uses the theory of public service innovation. The method used in this study is a descriptive qualitative method. The quality of public services in Indonesia in general is still relatively low, as can be seen from several indicators such as the level of public satisfaction, professionalism of human resources, the effectiveness and efficiency of the system used has not been managed properly. The findings of this study state that in the aspect of Leadership, the Head of the Investment and One-Stop Service Service carries out a democratic and transformative leadership style. In terms of management, mpp South Tangerang City has developed technology-based services to make it easier for residents. In terms of risk management, the South Tangerang City MPP early on mitigated the problem by improving the internet network. From the aspect of human capital, the human resources in the MPP of South Tangerang City have met academic qualifications, experienced, and competent. In terms of technology, the services contained in the Mpp of South Tangerang City are developed and can be accessed easily through various applications. This research concludes that the existence of a Public Service Mall in the city of South Tangerang has been running in accordance with orders from the direction of the Ministry of State Apparatus Empowerment and Bureaucratic Reform (KEMENPANRB) to present the latest innovations in modern, effective and efficient public services.